Production of Trash Cans from Used Masks (Not Health Facilities) in Suko Village, Sukodono District, Sidoarjo City (Nusantara Science and Technology Proceedings, 2021)
Suko Village is a village located in Sukodono District, Sidoarjo Regency, East Java Province with the majority of the livelihood being self-employed and partly formal workers. The Covid-19 pandemic has had a huge impact on jobs and masked waste. Employment income decreased and mask waste increased. The problem of mask waste afflicts the people of Suko Village. because of the lack of skills and knowledge possessed in the use of mask waste, the people of Suko Village cannot process a lot of mask waste. Meanwhile, for domestic waste management activities, both sporting and collecting waste, it is very embedded and cultured as well as committed in terms of managing the environment. Residents of RT 1 RW 1 Suko Village have participated in the collection of waste that still has a sale value. However, it is not optimal because temporary trash bins are always alkaline exposed to rainwater, and are not neat in the collection, which can affect the selling value of a waste product itself. The purpose of this activity is to use mask waste into a modified and applicable trash bin to be a supportive place for storing waste that has a selling value. In the implementation of this activity, several stages are carried out, namely planning, preparation, and implementation (training, product manufacture, and application use). The planning stage is an explanation of the design of the garbage bin. The preparation stage is the socialization of the benefits of the garbage bin. The implementation stage is conducting training in making garbage bins from masks. The mask waste goes through a chemical and physical sterilization process before use and changes its shape. Next is the activity evaluation stage. By using these 2 units of garbage bins, we were able to reduce the number of masks waste by 128 pieces of used masks. Each of these trash bins has a capacity of 0.16 m3. Storage conditions in dry and neat conditions increased sales of used bottles and paper by 14.5% from the previous month for bottles and cardboard.